Reinforcement learning for optimal feedback control : a Lyapunov-based approach /: a Lyapunov-based approach. (2018) - Kamalapurkar, Rushikesh; Walters, Patrick; Rosenfeld, Joel; Dixon, Warren E, 1972-
No abstract available